MeiosisOnline: A Manually Curated Database for Tracking and Predicting Genes Associated With Meiosis - Jiang, Xiaohua; Zhao, Daren; Ali, Asim; Xu, Bo; Liu, Wei; Wen, Jie; Zhang, Huan; Shi, Qinghua; Zhang, Yuanwei (Frontiers in Cell and Developmental Biology, 2021)
Meiosis, an essential step in gametogenesis, is the key event in sexually reproducing organisms. Thousands of genes have been reported to be involved in meiosis. Therefore, a specialist database is much-needed for scientists to know about these genes function quickly, and to search for genes with potential roles in meiosis. Here, we developed “MeiosisOnline”, a publicly accessible, comprehensive database of known functional genes and potential candidates in meiosis (https://mcg.ustc.edu.cn/bsc/meiosis/index.html). A total of 2,052 meiotic genes were manually curated from literature resource and were classified into different categories. Annotation information was provided for both meiotic genes and predicted candidates, including basic information, function, protein-protein interaction (PPI) and expression data. On the other hand, 165 mouse genes were predicted as potential candidates in meiosis using “Greed AUC Stepwise” algorithm. Thus, MeiosisOnline provides the most updated and detailed information of experimental verified and predicted genes in meiosis. Furthermore, the powerful searching tools and friendly interface of MeiosisOnline will greatly help researchers in studying meiosis in an easy and efficient way.